Electric and photophysical properties of holographic and electroluminescent media based on amorphous molecular semiconductors - Al-Kadhimi, A.J.; Davidenko, N.A.; Derevyanko, N.A.; Ishchenko, A.A.; Kuvshinsky, N.G.; Pavlov, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Results of investigations of electric and photophysical properties inherent to films of amorphous molecular semiconductors doped with different sensitizers of photoconductivity for visible light are discussed. Such films are used in electrography, holography and electroluminescent devices. The general regularities of charge carriers transport, electron-hole pair formation, charge carriers recombination are ascertained. Examples of the holographic recording media as well as media for electroluminescent devices are presented.